Differences in spatial distributions of iron supplementation use among pregnant women and associated factors in Ethiopia: evidence from the 2011 national population based survey. Issue 1 (December 2017) - Haile, Demewoz; Tabar, Lianna; Lakew, Yihunie
Abstract Background Iron supplementation during pregnancy prevents against low birth weight, incidence of prematurity and postpartum hemorrhage. However, the coverage of iron supplementation is still low in Ethiopia. This study aimed to investigate the spatial variations and associated factors of iron supplementation during pregnancy using the 2011 national demographic and health survey data. Methods This study used secondary data from the 2011 Ethiopian demographic and health survey. The survey was cross sectional and used a multistage cluster sampling procedure. A logistic regression statistical model using adjusted odds ratio (AOR) and 95% confidence interval (CI) was used to identify the associated factors. Getis-Ord G-statistic was used to identify high and low hotspot areas of iron tablet supplementation during pregnancy. Results The coverage of iron tablet supplementation was 17.1% [95%CI: (16.3–17.9)] with the highest coverage of 38.9% [95%CI: (32.4–46.1)] in Addis Ababa followed by Tigray regional state with 33.8% [95%CI: (29.9–38.00)]. The lowest coverage was found in Oromiya regional state at 11.9% [95%CI: (10.7–13.0)]. Multivariable analysis showed that mothers who were aware of the Community Conversation Program had 20% [AOR = 1.2; 95% CI: (1.04–1.4)] higher odds of taking iron tablets. The odds of taking iron tablets was 2.9 times [AOR = 2.9; 95% CI: (2.3–3.7)] higher among those who took deworming tablets. Those mothers who attended the minimum four antenatal visits recommended by WHO were 3.9 times [AOR = 3.9; 95% CI: (3.3–4.6)] more likely and those mothers in the age group 31–49 years were 2.9 times [AOR = 2.9; 95% CI: (1.1–7.4)] more likely to use iron tablets as compared to those mothers who did not attend antenatal care and mothers in the age group less than 20 years. Mothers having a family size of 10 and above had 32% [AOR = 0.68; 95% CI: (0.49–0.97)] lower odds of taking iron tablets during pregnancy. The spatial analysis found that only northern, central and eastern parts of Ethiopia were identified as hotspots of iron supplementation. Conclusion Iron supplementation use was not equally distributed in Ethiopia, with relatively higher prevalence in Tigray, Addis Ababa and Harari regional states. Attention should be given to younger age mothers, mothers with large family size and mothers who reside in areas with low coverage of iron tablet distribution. Promotion of antenatal care services based on the WHO standard can be used as an intervention for improving iron supplementation during pregnancy.